Structural and Reliability Analysis of the Vietnamese Perceived Faculty Support Scale: Evidence for a Unidimensional Construct - Ngoc Tuyet Le; Trung V. Nguyen (Journal of Nursing Measurement, 2026)
Background and Purpose: The Perceived Faculty Support Scale (PFSS) is one of the few instruments designed to assess faculty support. This study aimed to translate the scale into Vietnamese and evaluate its validity and reliability among nursing students. Methods: This cross-sectional study yielded a cross-cultural translation for the PFSS using convenience sampling. The validity of the Vietnamese version of the PFSS (PFSS-V) was assessed through face validity, content validity, construct validity using exploratory factor analysis (EFA), concurrent validity, and known-group validity. Coefficient alpha and an intraclass correlation coefficient (ICC) were used to assess internal consistency and score stability, respectively. Results: The PFSS-V demonstrated good content validity. EFA revealed a one-factor structure explaining 80.04% of the variance, with all items loading strongly. Concurrent validity was evidenced by a significant positive correlation between PFSS-V scores and self-efficacy in learning and performance. Nursing students’ PFSS-V scores improved as they increased in age, school year, and grade point average. The scale exhibited excellent reliability, with a coefficient alpha of .98 and an ICC of .83 (95% confidence interval [0.62, 0.93]). Conclusions: The PFSS-V is a unidimensional and reliable tool for assessing nursing students’ perceived faculty support.